Perancangan dan Pembuatan Aplikasi SIMPORA Berbasis Online dengan PHP - Bakti, Firdaus, Masduki, Indra , Mohamad , Uki (Technologia Journal, 2024)
The Tanjung Pandan Customs Office as a State Agency has the opportunity to compete with other customs in Indonesia, as an added value for the Tanjung Pandan Customs Office in its office at the Customs Agency. SIMPORA as an information system for Budget Absorption and Realization was created to meet these needs. The application design in this study was built using the Unified Software Development Process method and the application design used the Unified Modeling Language (UML). This software project iteratively (repeating steps, as feedback from the user) starts from the process of making Software Requirements Design (SKPL), then proceeds with making Software Design (DPPL), then followed by making applications and closing with testing. This process is carried out continuously according to the planning period. The result of this project is software that is also equipped with design and application documentation which in the end is to give the Tanjung Pandan Customs office a winner in the competition between customs offices throughout Indonesia.